Penyelesaian Sengketa Bidang Perbankan Pasca Beralihnya Fungsi Pengaturan dan Pengawasan dari Bank Indonesia ke Otoritas Jasa Keuangan (OJK) - Anjar Permana Sidik (JURNAL PEMULIAAN HUKUM, 2019)
Banking institutions is at the core of the financial system of each country. Bank is a financial institution that is home to natural persons, private enterprises and the state. Through the activities of credit and various other services, banks participating in the payment mechanism for all sectors of the economy. Activities fund for banks in the communities it covers transactions in credit purchases, utilization of the means of bank facilities such as the provision of credit cards, ATM, securities and others, position of the bank is an institution that is closely linked to the community and has a reciprocal relationship with the community itself in accordance with the framework of principles of banking law. How to Position and Role of the Financial Services Authority in the Settlement of Disputes for Banking, after the passing of Banking Supervision of Bank Indonesia to FSA? And How Contributions Authority financial services in settlement disputes and banking supervision in Indonesia? The research method is descriptive analysis, with normative juridical approach, which uses the primary data source is secondary data obtained through the study of documents, this study conducted two phases: the first phase of the research literature, with data collection technique using studies document that further secondary data analyzed juridical qualitative, then the second stage to add additional data to the object and continued to interview discussed. The author of the research results can find and conclude the following: the Status and Role Services Authority finances in the settlement of disputes between customers and banks through alternative dispute resolution after the transfer of the functions of banking upervision from Bank Indonesia to the financial services authority greatly assist the parties to the dispute either customer or bank to resolve the issue through consultation, Negotiation, Mediation, Conciliation and Adjudication and Arbitration for in Law No. 21 Year 2011 on the Financial Services Authority, the protection of customers  are protected and included in the defense of the law, in contrast to the settlement of disputes through Bank Indonesia, which only provides a place without any recommendation or decision of the Bank of Indonesia.  In the Banking Law legal relationship between the customer and the bank is not mentioned clearly so in case  of a dispute the parties is hard to find completion. With the effective enactment of Law No. 21 Year 2011 concerning FSA Legal Protection of either the customer or the bank can be protected.